Model Trend Parabola untuk Memproyeksi Jumlah Kematian Bayi dan Balita yang Terdata di Badan Pusat Statistik Provinsi NTT Tahun 2023 - Melki Imamastri Puling Tang (Universitas Merdeka Malang, 2022)
Researchers projected data on the number of child and under-five deaths recorded at the East Nusa Tenggara Province BPS using the parabolic trend model. The data reference used is BPS data for the province of East Nusa Tenggara from 2016 to 2020. Based on the analysis of the researcher's data, it was found that the number of cases of infant and under-five deaths in 2021 recorded in the NTT BPS data was 346.5 people. the number of cases of infant and under-five deaths in 2022 recorded in the BPS NTT data was 1,054.63 people, and the number of cases of infant and under-five deaths in 2023 recorded in the NTT BPS data was 2,457 people. The researcher concluded that there was an increase in awareness from the public to take medical action and also the seriousness of the medical staff to record properly and increase work discipline. It is also necessary to take strategic steps to reduce the number of child and under-five mortality cases in East Nusa Tenggara province.